The Artificial Insemination Pregnancy Program as a Type of Service and Level of Efficiency of Health Services - Berly Nisa Srimayarti; Devid Leonard; Dicho Zhuhriano Yasli; Linda Handayuni (Postgraduate, University of Mataram, 2023)
The purpose of this study is to look at the artificial insemination pregnancy program service as one of the services at Mutiara Bunda Mother and Child Hospital. In this context, it will also look at the perspective of its management efficiency. The pregnancy program with this method involves the age of female and male patients, endometrial thickness (EMT), post-washing total motile sperm count (PTMC), artificial insemination time, insemination frequency, and ovarian stimulation protocol which are compared between the pregnant group and the non-pregnant group to see any correlation. Then, hospital efficiency reflects the ratio of the value of health services provided, both quantity and quality of care to the resources used in health services. This study was conducted at Mutiara Bunda Mother and Child Hospital Padang. The results of the study state that procedurally and institutionally, the pregnancy program service with artificial insemination at RSIA Mutiara Bunda Padang is very good. Specialist doctors and other paramedics are well qualified to implement this service program. The Director of the Mother and Child Hospital includes effective leadership because the performance of staff or officers at the Mother and Child Hospital has worked well, with the motivation provided by the leadership. The hospital has adequate specialist doctors, both in terms of number and type of specialization in accordance with hospital specifications, namely Obgyn and Pediatric specialists. The artificial Insemination Pregnancy Program as a type of service is the first in Padang